Spatial Turn and Situational Approach: Ethical Dimension - Інна Голубович; Катерина Павленко (Cхід, 2023)
The article is devoted to the explanation of the basic principles of the situational approach in the light of the modern "spatial turn", presented to the scientific community by the ideas of such world-famous modern theorists as D. Harvey and A. Lefebvre. Our main focus is the ethical dimension of the outlined problem field. The starting point is the ancient presumption of the etymological and semantic unity of ethos and space. The authors of the article conceptualize this synthetic unity, offer a set of certain principles and theoretical assumptions. The main result of the study is the interpretation of the situation as a space of a responsible individual act, a field of equal interaction of the individual with the external environment, circumstances, conditions, as well as a state of existence of a “specific material a priori/ a priori scene”. The authors formulate the following principles of situational vision: a) the primacy of the individual, the existential situation and the secondary nature of any external circumstances and conditions; b) the principle of “primary historicity”; c) the principle of “limit situation” as a transcendental-immanent unity; d) the principle of the situation as a mode of “a priori scene”. The most important constitutive procedures of the situation as a topos of the act of individuation are described: interiorization and immanentization, namely, situational and personal interiorization of the meaning of the main civilizational cultural-historical conflicts and immanentization of general ethical norms in one's own individual semantic field. The thesis is substantiated that the spatial-situational discourse has significant heuristic resources for the analysis of current socio-cultural and political processes in the modern world.